Conhecimento dos profissionais da atenção primária à saúde sobre a síndrome da fragilidade no idoso: um estudo transversal - Mesquita, Wesley dos Reis (2020)
Introduction: Frailty is a dynamic and multifactorial geriatric syndrome characterized by the cumulative decline of multiple systems. The care provided by the Primary Health Care is important for actions on prevention and intervention in the frailty syndrome, avoiding health complications to the older adults and the increase need for care and health expenses. Objective: To verify the knowledge of health care professionals in the context of Primary Health Care regarding the frailty syndrome. Methods: Crosssectional observational study conducted in the Primary Health Care in the State of Minas Gerais. Graduate professionals who work at the Family Health Strategy and the Family Health Support Nucleus teams for at least 6 months and who assist older adults in their clinical practice were included. Data collection was performed electronically, through a questionnaire about professional training, performance in the Primary Health Care and knowledge of the frailty syndrome. Data were analyzed descriptively and by association, correlation tests and logistic regression. Results: Sample of 485 professionals, mostly nurses (62.9%), female (83.3%) and average age of 35.9±7.2 years. Over half of the professionals self-reported (52.6%) little or no knowledge about the syndrome and demonstrated low practical knowledge (55.1%) by identifying a clinical case. The type of knowledge with the worst result was the theoretical one, with 87.5% of the professionals incorrectly describing the syndrome. There was no agreement between self-reported, theoretical and practical knowledge. The professionals presented misconceptions about frailty, as this is the result of aging (83.3%) and is synonymous of disability, comorbidity and advanced age (51.2%). Most were unaware of instruments for assessing frailty (77.9%) and the phenotype criteria (68.2%). According to the professionals, the main difficulty in implementing actions in Primary Care for the prevention and intervention of frailty is the lack of trained professionals (63.1%) and the preferred way to acquire this knowledge is face-to-face courses (62.9%). Professionals with specialization or training/ qualification courses in older adult care have 6.1 and 2.7 more chances, respectively, to self-report having some knowledge about the frailty syndrome. Conclusions: Higher education professionals in Primary Care have little knowledge about frailty syndrome. To face this condition in the community setting is essential to training these professionals.